5 European & African Conference on Wind Engineering - Augusti, Giuliano; Borri, Claudio; Bartoli, Gianni; Facchini, Luca (Proceedings e report, 2009)
The 5th European-African Conference of Wind Engineering is hosted in Florence, Tuscany, the city and the region where, in the early 15th century, pioneers moved the first steps, laying down the foundation stones of Mechanics and Applied Sciences (including fluid mechanics). These origins are well reflected by the astonishing visionary and revolutionary studies of Leonardo Da Vinci, whose kaleidoscopic genius intended the human being to become able to fly even 500 years ago... This is why the Organising Committee has decided to pay tribute to such a Genius by choosing Leonardo's "flying sphere" as the brand of 5th EACWE.